INFLUENCE OF EDUCATIONAL TRAJECTORIES ON THE FORMATION OF THE MANAGERIAL ELITE IN THE RUSSIAN FEDERAL AUTHORITIES - N. A. Yushkina (Вестник университета)
The analysis of features of educational trajectories of representatives of Federal managerial elite of Russia has been carried out and their specificity has been defined. The biographies of 370 deputy heads of federal departments and 67 biographies of heads of federal departments were taken as a basis. According to the results, a high educational level and a number of preferences of the managerial elite have been identified, a pool of leading universities involved in personnel training has been highlighted. The special role of the Russian Presidential Academy of National Economy and Public Administration has been noted as a forge of managerial personnel and a mechanism for consolidating social status for representatives of the managerial elite. It has been supposed, that a doctorate degree is one of the conditions for getting into the managerial elite. The universality of the application of economic, legal and managerial education in the field of federal government of the country makes these profiles especially attractive for representatives of the managerial elite. The growth of managers with a universal education profile leads to the replacement of specialists with specialized education by them, and this is alarming. Universal education is becoming a certain condition for joining the state’s management elite, as well as a possible way to adjustment of the compliance education to changing career paths.